Integration of Data and Perception in Diarrhea Surveillance Reporting: A Mixed-Methods Study in Indonesia - Hesty Latyfa Noor; Indra Agung Yudistiro; Puguh Ika Listyorini; Kinanti Anggraini; Denistism Egi Armadani (International Journal of Health and Social Behavior, 2026)
Surveillance for diarrhea at the district level in Indonesia is still affected by the fragmented nature of the District Health Information System (DHIS) and Early Warning and Response System (EWARS), inconsistent reporting, patchy data interoperability, and the resulting public health delays. Although there are systems in place like the DHIS and EWARS, the persistent use of hybrid systems that combine manual and digital data entry, as well as the different skill levels of users, continues to produce issues of incompleteness, untimely reporting, and inaccurate data. The present study investigated the deficiencies in surveillance reporting of diarrhea cases, the surveillance data to determine the degree of integration and also investigated the health workers perceptions of the barriers to effective reporting. A mixed methods approach was adopted in this study where we investigated quantitatively the DHIS and routine diarrhea reports submitted for the entire year of 2023, and combined that with qualitative, in-depth interviews with the relevant surveillance officers, program managers, and district staff. The quantitative analysis indicated gaps in reporting about 55% in terms of completeness, and consistency of reporting and also significant differences were found between the manual register, DHIS, and EWARS whereby the integration of these systems was found to be low. The qualitative analysis pointed to the combination of disconnected workflows, limited cross-system interoperability, inadequate system training, excessive workloads, and weak organizational feedback, as the main barriers to effective reporting. The combination of these two datasets illustrates the fact that both system deficiencies and organizational factors are primary drivers of the reporting. Closing the gaps will require system level changes in the interoperability of reporting systems, simplified reporting workflows, training, reporting, and reporting feedback loops.